Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Kesejahteraan Masyarakat Kabupaten Jeneponto - Nur Aisyah Qadri Saiful (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
Welfare is closely related to the goals of the Indonesian State. The state is established, maintained and developed for the benefit of all the people, namely to guarantee and advance the general welfare. Low income means that people cannot access education and health due to limited costs. Based on this background, this research was conducted with the title "Analysis of the factors that affect the level of welfare of the Jeneponto Regency community". This research was conducted in July - September 2020 in Jeneponto Regency and the income was based on household expenses. The type of data used in this research is quantitative data which is data that can be processed or analyzed using statistical calculation techniques. The research method used is descriptive and explanatory research methods. The data analysis technique used in this study was to determine the factors that affect the level of community welfare in Jeneponto Regency, namely multiple linear regression analysis. The results of the analysis show that the life expectancy rate does not have a significant effect on the level of human welfare (HDI) and the average length of schooling has a significant effect on the level of human welfare.